Improved surgical margin definition by narrow band imaging for resection of oral squamous cell carcinoma: A prospective gene expression profiling study. Issue 6 (26th June 2015) - Farah, Camile S.; Dalley, Andrew J.; Nguyen, Phan; Batstone, Martin; Kordbacheh, Farzaneh; Perry–Keene, Joanna; Fielding, David
ABSTRACT: Background: Incomplete primary tumor excision contributes to localized postsurgical recurrence of oral squamous cell carcinoma (OSCC). The purpose of this study was to provide molecular evidence that surgical margin definition using narrow band imaging (NBI) resulted in more complete OSCC excision than conventional white light (WL) panendoscopy. Methods: Molecular divergence among tumor, WL, and NBI‐defined surgical margins was compared in 18 patients through microarray analysis (GeneChip U133‐plus‐2.0). Results: The numbers of differentially expressed genes (NBI = 4387; WL = 3266; vs tumor) signified that NBI placed margins into less involved tissue than WL examination. Principal component analysis segregated tumor, WL, and NBI tissues appropriately based solely on mRNA profiles, and unsupervised hierarchical clustering identified 4 patients (22%) who benefited directly from NBI surgical margin definition. Gene ontology enrichment indicated increasing cell phenotypic diversity: tumor<WL<NBI. Conclusion: Resection to NBI‐defined margins will leave less dysplastic and malignant residual tissue and thereby increase ablative surgery success rates. © 2015 Wiley Periodicals, Inc. Head Neck 38: 832–839, 2016